Supercritical carbon dioxide (SC-CO2) extraction and fractionation of palm kernel oil from palm kernel as cocoa butter replacers blend - Sarker, Md. Zaidul Islam; Nik Ab Rahman, Nik Norulaini; Abd Kadir, Mohd Omar; R. L., Smith Jr. (Elsevier Inc., 2006)
Application of supercritical carbon dioxide (SC-CO2) to fractionate shorter-medium (C8–C14) and longer chain (C16–C18:2) triglycerides in terms of fatty acid constituents in palm kernel oil (PKO) was studied for formulating possible cocoa butter replacer blends. The extraction of PKO from dehulled ground palm kernel was carried out at 40 and 80 C and pressures ranging from 20.7 to 48.3 MPa with a flow type apparatus. The PKO was extracted successively into four fractions. At higher temperatures (80 C) the total yield of PKO increased with pressure. The highest yield (99.6%) was obtained at 48.3 MPa and 80 C with minimum CO2 used. Much shorter chain C8, C10, C12 fatty acid constituents were extracted in fraction 1. Longer chain 16, C18:0, C18:1 and C18:2 fatty acid constituents were extracted in fraction 4. The slip melting points were reduced to be between 8 and 10 C for fractionated PKO in the latter fractions. The Lovi bond colour of these fractions was less intensive than the earlier fractions. The latter fractions had triglycerides in terms of fatty acid constituents, slip melting point, solid fat content, iodine value, saponification value and acid value closer to those of cocoa butter replacer blends.